Growth and photosynthetic down-regulation in Coffea arabica in response to restricted root volume - Ronchi, Claudio P.; DaMatta, Fabio M.; Batista, Karine D.; Moraes, Gustavo A. B. K.; Loureiro, Marcelo E.; Ducatti, Carlos (CSIRO Publishing, 2006)
Coffee (Coffea arabica L.) plants were grown in small (3-L), medium (10-L) and large (24-L) pots for 115 or 165 d after transplanting (DAT), which allowed different degrees of root restriction. Effects of altered source : sink ratio were evaluated in order to explore possible stomatal and non-stomatal mechanisms of photosynthetic down-regulation. Increasing root restriction brought about large and general reductions in plant growth associated with a rising root : shoot ratio. Treatments did not affect leaf water potential or leaf nutrient status, with the exception of N content, which dropped significantly with increasing root restriction even though an adequate N supply was available. Photosynthesis was severely reduced when plants were grown in small pots; this was largely associated with non-stomatal factors, such as decreased Rubisco activity. At 165DAT contents of hexose, sucrose, and amino acids decreased in plants grown in smaller pots, while those of starch and hexose-P increased in plants grown in smaller pots. Photosynthetic rates were negatively correlated with the ratio of hexose to free amino acids, but not with hexose content. Activities of acid invertase, sucrose synthase, sucrose-P synthase, fructose-1,6- bisphosphatase, ADP-glucose pyrophosphorylase, starch phosphorylase, glyceraldehyde-3-P dehydrogenase, PPi : fructose-6-P 1-phosphotransferase and NADP : glyceraldehyde-3-P dehydrogenase all decreased with severe root restriction. Glycerate-3-P : Pi and glucose-6-P : fructose-6-P ratios decreased accordingly. Photosynthetic down-regulation was unlikely to have been associated directly with an end-product limitation, but rather with decreases in Rubisco. Such a down-regulation was largely a result of N deficiency caused by growing coffee plants in small pots.
Keywords: coffee; nitrogen deficiency; pot size; Rubisco; sink regulation